Impact of Rotylenchulus reniformis on Cotton Yield as Affected by Soil Texture and Irrigation - Herring, Stephanie L (Journal of nematology, 2010)
The effects of soil type, irrigation, and population density of Rotylenchulus reniformis on cotton were evaluated in a two-year microplot experiment. Six soil types, Fuquay sand, Norfolk sandy loam, Portsmouth loamy sand, Muck, Cecil sandy loam, and Cecil sandy clay, were arranged in randomized complete blocks with five replications. Each block had numerous plots previously inoculated with R. reniformis and two or more noninoculated microplots per soil type, one half of which were irrigated in each replicate for a total of 240 plots. Greatest cotton lint yields were achieved in the Muck, Norfolk sandy loam, and Portsmouth loamy sand soils. Cotton yield in the Portsmouth loamy sand did not differ from the Muck soil which averaged the greatest lint yield per plot of all soil types. Cotton yield was negatively related to R. reniformis PI (initial population density) in all soil types except for the Cecil sandy clay which had the highest clay content. Supplemental irrigation increased yields in the higher yielding Muck, Norfolk sandy loam, and Portsmouth loamy sand soils compared to the lower yielding Cecil sandy clay, Cecil sandy loam, and Fuquay sand soils. The Portsmouth sandy loam was among the highest yielding soils, and also supported the greatest R. reniformis population density. Cotton lint yield was affected more by R. reniformis Pi with irrigation in the Portsmouth loamy sand soil with a greater influence of Pi on lint yield in irrigated plots than other soils. A significant first degree PI × irrigation interaction for this soil type confirms this observation